Development of an Anti-Cheating Online Examination System at MTs Assulaimaniyyah: Pengembangan Sistem Ujian Daring Anti-Kecurangan di MTs Assulaimaniyyah - Sri Widaningsih; Agus Suheri; Muhamad Juanda (FKOM UNIKU, 2026)
Digital transformation in the field of education encourages the implementation of online examination systems to improve the effectiveness and efficiency of the learning evaluation process. However, the implementation of online exams still has weaknesses, especially related to supervision and the potential for cheating by exam participants. This study aims to develop a web-based online examination system with anti-cheating features at MTs Assulaimaniyyah. The system development method used is the waterfall method, which consists of the stages of communication, planning, modeling, construction, and deployment. The system was built using the PHP programming language with the Laravel framework and a MySQL database. The anti-cheating features implemented include fullscreen mode, prevention of copy-paste actions, prohibition of using two screens, screenshot restrictions, question randomization, exam time limitations, and tab-switching detection that can cause the exam to stop automatically. The results of the study show that the system is capable of helping the exam implementation process become more effective, simplifying the management of questions and exam results, and improving supervision during the exam. With the anti-cheating features, the system can support the creation of a more honest, fair, and accurate evaluation process, thereby contributing to the improvement of educational quality